Unilateral Claim in Dispute of Island Over the South China Sea - Muhammad Nasir; Wan Siti Adibah Wan Dahalan; Harun Harun; Phoenna Ath Thariq (Sriwijaya Law Review, 2020)
In the unilateral claim, every determination of a territory is the right of a sovereign state and does not require agreement with international organizations or other countries. Especially regarding the borders of a country, many international regulations require a joint determination (bilateral or multilateral). The norm will impact the absence of responses from another country, or such a country does not react because its interests were not disturbed. China's unilateral statement over the South China Sea has tried to dominate globally, and at the same time, there has been no stabilization of peace. It will likely continue, expand, and have long-term adverse impacts on the regional economic and security situation in the region. China's unilateral claims in the South China Sea have also resulted in other warring countries, strengthening their presence and claims. This research uses normative approach which examines the unilateral claims under international law in the South China Sea especially in the UNCLOS 1982 and other related international law instruments. As a result, for China, it is necessary to improve its current position, at least it needs to negotiate in the future. Countries which is involved in the South China Sea should clarify and submit territorial claims and maritime rights under international law, including the UNCLOS 1982.